P266 At What Rate Does New Evidence Change Guidance. (15th August 2013) - Ording, J; Thiese, M; Hegmann, K; Wolfkiel, C; Ott, U
Abstract : Background: New research is continually shaping guidelines; however, the rate of change has not been assessed. Objectives: Review articles from 2010 to 2013 to assess rate of change of guidelines for the elbow. Methods: A systematic literature search was conducted to identify randomised controlled trials (RCTs) on elbow disorders published between 2010 and 2013. Identified RCTs were scored using established scoring methods and incorporated into guidelines to determine if any recommendations needed to be changed or new recommendations added. Results: Fifteen new RCTs were identified (4 high-, 9 moderate-, and 2 low-quality). Nine (69%) studies were used to make 3 new recommendations and 4 changes to recommendations to guidelines on elbow disorders. Seven of these studies prompted new guidance on soft tissue mobilisation, autologous blood injections, periarticular blood injections for lateral epicondylalgia (LE). Two of these studies caused changes to the recommendation level for manipulation/mobilisation for LE and evidence level changes for exercises, glucocorticosteroid injections, and platelet rich plasma injections for LE. Seven (53%) studies did not change any of the recommendations but added to the body of evidence to support the current recommendations. Discussion: New studies may be higher quality and have significant impact on guidelines. Two-thirds of new evidence triggered recommendations changes or development of new recommendations for treating LE. Additional assessments of low back and other body parts are underway. Implications for Guideline Developers/Users: It is beneficial to do a yearly review of the literature to determine if any new evidence will impact changes to current guidelines.